31.6k views
2 votes
What are the two solutions of 2x2 = –x2 – 5x – 1?

2 Answers

0 votes

Answer: ITS C!!!!!!!

Explanation:

User Jo Liss
by
4.4k points
2 votes

Answer:

The answer is


x = ( - 5 + √(13) )/(6) \: \: \: \: or \: \: \: x = ( - 5 - √(13) )/(6)

Explanation:

2x² = - x² - 5x - 1

Rearrange the terms and simplify

That's

2x² + x² + 5x + 1 = 0

3x² + 5x + 1 = 0

Using the quadratic formula solve the equation

That's


x = \frac{ - b\pm \sqrt{ {b}^(2) - 4ac} }{2a}

From the question

a = 3 , b = 5 , c = 1

So we have


x = \frac{ - 5\pm \sqrt{ {5}^(2) - 4(3)(1) }}{2(3)} \\ = ( - 5\pm √(25 - 12) )/(6) \\ = ( - 5\pm √(13) )/(6)

We have the final answer as


x = ( - 5 + √(13) )/(6) \: \: \: \: or \: \: \: x = ( - 5 - √(13) )/(6)

Hope this helps you

User Hunse
by
5.2k points